Imaging Following Fractures of and Around the Knee - Sanal, Hatice Tuba; Krestan, Christian; Schurz, Mark (Seminars in Musculoskeletal Radiology, 2018)
Related to fractures of and around the knee, inappropriate technical factors related to the surgery, severe comminution of the fracture, early overly arduous rehabilitation of the patient, and patient-related noncompliances may have the potential for the risk of inadequate fixation and other complications. Loss of fixation, malunion/nonunion, infection, arthritis, arthrofibrosis, and symptomatic hardware are among postsurgical complications that may necessitate further reconstructive techniques. In this review, complications that may be encountered in the postsurgical period of fractures involving the patella, supracondylar femur, and tibial plateau are described.
Keywords: postoperative; surgery; complications; knee; patellar; femoral; supracondylar; tibial plateau; fracture